2018
DOI: 10.1002/bab.1707
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐26a and miR‐21 as biomarkers for glioblastoma multiform

Abstract: Glioblastoma multiform is the most common and lethal primary central nervous system tumor. Circulating microRNAs (miRNAs), present in cell-free bodily fluids, have been gaining importance as cancer biomarkers. The primary aim of this study was to assess whether circulating miRNA-128, -21, and -26a in glioblastoma patients can be used as diagnostic biomarkers. Venous blood samples were collected from 11 noncancerous volunteers and 15 glioblastoma patients preand post operation. Also, tissue tumor samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Five miRNAs were found to be involved in MGMT alterations and tumor suppressor functions of TP53 (miR-21, miR-125b, miR-34a, miR-181d, and miR-648) in GBM progression ( 38 ). In particular, miR-21 and miR-181d were associated with GBM tumorigenesis ( 39 42 ), as have a number of other miRNAs, miR-144 and miR-29a ( 43 45 ). These miRNAs may prove to be important biomarkers for GBM, but their specificity needs to be further validated.…”
Section: Genomic Landscape Of the Gbm Microenvironmentmentioning
confidence: 99%
“…Five miRNAs were found to be involved in MGMT alterations and tumor suppressor functions of TP53 (miR-21, miR-125b, miR-34a, miR-181d, and miR-648) in GBM progression ( 38 ). In particular, miR-21 and miR-181d were associated with GBM tumorigenesis ( 39 42 ), as have a number of other miRNAs, miR-144 and miR-29a ( 43 45 ). These miRNAs may prove to be important biomarkers for GBM, but their specificity needs to be further validated.…”
Section: Genomic Landscape Of the Gbm Microenvironmentmentioning
confidence: 99%
“…We selected miR-20a and miR-26a for analysis based on previous impellent studies which described the importance of these miRNAs in cancers (ParvizHamidi et al, 2018;Xu et al, 2018). For example there are studies expressed that miR-20a regulates cell growth and plays important roles in prostate and other cancers initiation and progression (O'donnell et al, 2005;Pesta et al, 2010;Liu et al, 2012;Xu et al, 2018;Zhang et al, 2018).…”
Section: Circulating Mir-20a and Mir-26a As Biomarkers In Prostate Camentioning
confidence: 99%
“…The first evidence that miRNAs can be found also in extracellular body fluids, incorporated into microvesicles, or bound to specific RNA-binding proteins, came from Skog et al [45]. This study paved the way for the use of miRNAs as potential non-invasive diagnostic biomarkers for GBM [46][47][48][49][50][51]. The involvement of miRNAs in GBM cell resistance to chemotherapy was first reported by Li et al [52]; they showed that oncomiR-21 is involved in GBM cell resistance to the chemotherapeutic agent teniposide by targeting LRR binding FLII interacting protein 1 (LRRFIP1) mRNA.…”
Section: Micrornas (Mirnas) Are Extensively Dysregulated In Gbmmentioning
confidence: 97%